ECONOMIC CRIME IN THE POLISH LEGAL SYSTEM ON THE EXAMPLE OF THE CRIME OF OBTAINING A BANK CREDIT BY FALSE PRETENCES - Krzysztof, Mucha (Anales Universitatis Apulensis Series Jurisprudentia, 2013)
The analysis of one of the types of economic offences occurring in the Polish legal system presented herein allows to state that law enforcement agencies have an effective possibility of preventing this illpractice. Furthermore, the problem presented clearly indicates how the Polish legal system reduces this kind of crime. It seems that considering the vision of another economic crisis, economic offences, inclusive of the analyzed credit fraud, will be more and more frequently a subject of penal proceedings conducted in Poland. Keywords: economic crimes, bank credit, banking institutions, credit fraud